Cinema, literatura e subjetividade: uma leitura feminista dos (con)textos Blade Runner - Guidoni, Patricia (2021)
This research uses the minor literature as an epistemology for the development of a feminist critical analysis of the texts of “Blade Runner”. The concept of subjectivity is considered from Suely Rolnik’s perspective in the work “Spheres of insurrection: notes for a non-pimped life” (2019) using, mainly, the concepts of colonial-capitalistic unconscious and reactive micropolitics with aims to relate these concepts to the possible readings of works (texts) Do Androids Dream of Electric Sheep? (1968), Blade Runner (1982) and Blade Runner 2049 (2017), in which the colonial-capitalistic force of mainstream productions, mass culture, tend to produce a reactive, reterritorializing micropolitics on one of the most enthusiastic issues today, feminism. Also, it will be used the concept of active micropolitics that intends to deterritorialize the current regime through collective, artistic forces, etc. so that it is possible to reappropriate the force of creation and cooperation, a force that enables to resist the dominant regime in ourselves. Therefore, the minor literature appears as a possibility of insurgency of a feminist criticism that seeks to produce echoes in the active micropolitics by calling for, in the hybrid re(write) of the characters, the minorization of a larger language. Feminism appears as the possibility of breaking with the established scene that mainstream productions tend to reterritorialize. There are two revolutions in progress, feminism and the production of subjectivity, which support the tension that destabilizes them for the germination of new worlds, decolonization of the unconscious.